Effects of concurrent training on heart rate variability in sedentary and trained healthy young adults - David Cobos-Valiente; Gemma María Sánchez-Bernal (Journal of Sports and Physical Activity, 2026)
Background: Heart Rate Variability (HRV) has been established as a reliable and useful indicator of autonomic regulation and the specific physiological responses of the body to physical exercise. Aims The objective of this pilot study was to describe the specific differences in HRV responses between trained and sedentary healthy young adults before and after a concurrent training session. Methods The researchers employed a quasi-experimental design with descriptive analysis involving four participants categorized by their training status. HRV data was recorded at rest through photoplethysmography, while the concurrent training protocol integrated both resistance and endurance exercises with intensity monitored via the rating of perceived exertion scale. Results The findings indicated that trained participants possessed higher baseline HRV values and experienced a smaller decrease in HRV following exercise compared to the sedentary group. Furthermore, the trained individuals demonstrated an apparently faster recovery rate after the training session was completed. Conclusion The study suggests that prior training status may significantly influence the acute autonomic response to concurrent training. However, due to the small sample size and descriptive nature of the study, these results are considered preliminary and should be interpreted with caution, highlighting the need for future research with larger samples to confirm these patterns.